Розвиток внутрішньополітичних процесів у Косово (1999-2017 рр.) - Павленко, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
У статті проаналізовано внутрішньополітичний розвиток Косово
після війни 1999 р. й проголошення незалежності 2008 року. Ключовою
проблемою внутрішньої політики є неврегульованість відносин із Сербією. Конфліктними залишаються албансько-сербські відносини у внутрішній політиці Косово. Суверенітет Косово офіційно перебував під
протекторатом ООН і НАТО в 1999–2008 роках. Інтенсивне становлення внутрішньополітичних інституцій і партійних суб’єктів відбулося
впродовж 2008–2011 років. Економічні проблеми, зовнішня нестабільність на Балканах, незавершене міжнародне визнання залишають Косово
у стані держави, яка балансує на межі кризи. Стабільність забезпечується завдяки зовнішній підтримці з боку ООН, ЄС, НАТО, США. Influence of Yugoslavia’s collapse, as well as of external factors on
Kosovo’s separation from Serbia is explored in this article. Particular features
of Kosovo’s internal policy development and problems with a full international
recognition of its independence are also highlighted. The problem of Kosovo’s
status within the diplomacy of “power poles” in modern international relations
system in the context of NATO’s war against Yugoslavia in 1999 is underlined.
Kosovo is a multi-party parliamentary representative democratic republic.
The State is governed by legislative, executive and judicial institutions which
derive from the Constitution adopted in June 2008, although until the Brussels
Agreement, North Kosovo was largely controlled by institutions of the Republic
of Serbia or parallel institutions, funded by Serbia. The legislative power in
Kosovo is held by Parliament. The executive authority is vested in the
Government, headed by Prime Minister. The President is Head of State and
represents the unity of the people, elected every five years, indirectly by the
National Assembly, in a secret ballot by a two thirds majority of all deputies of
the Assembly.
Key trends in Serbian policy towards Kosovo after the democratic transformation
of its political system and in conditions of Serbia’s aspirations for
European integration was examined. The process of Kosovo’s recognition has
shown that Kosovo is an irreversible reality and an essential factor for peace
and stability in the Balkan region. This could be best proved by the recognition
of Kosovo among all neighboring countries (except Serbia), by the vast
majority of the countries in the region and the Euro-Atlantic community.